Saneamento rural no Brasil: A universalizaç\~ao é possível? - César Nunes de Castro; Monise Terra Cerezini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The supply of drinking water and the proper disposal of waste generated by human activities are two important factors that influence the quality of life and health of a population. In recent decades, access to basic sanitation services has shown advances in all Brazilian regions. Despite this, access to these services by the Brazilian population is still far from ideal. The Federal Constitution of 1988 includes basic sanitation as a right of the Brazilian population. Currently, 2023, the universalization of access to basic sanitation services is still far from reality. The distance from this universalization is even more distant in rural areas. Due to factors such as insufficient financial resources and the lower population density in rural areas, making it more expensive to provide basic sanitation services for a dispersed population, universalizing access for this group of people constitutes a complex task. The fiscal difficulties of the different federative entities in the last decade, especially the Federal one, constitute, perhaps, the main obstacle to the expansion of access. Financial execution data of investments related to rural sanitation from 2012 to 2022 demonstrate the significant reduction in invested amounts.
Keywords: L50; Q25; Q28; 330; sanitation; countryside; universalization